Synthesis of Marine Adhesive Proteins Secreted from Chilean Mussel - YAMAUCHI, Shigeru; IKEDA, Kengo; YAMAMOTO, Hiroyuki (KOBUNSHI RONBUNSHU, 1991)
The adhesive proteins (Ala-Gly-Tyr-Gly-Gly-X-Lys) n (X, Ala and Ile) secreted from Chilean mussel, which have the shortest hepta-repeating units, have been synthesized by fragment coupling followed by polycondensation of the active esters. The n of the natural proteins is about 160, whereas those of the synthetic proteins were 17-24. The Tyr residues can be modified to Dopa by the use of tyrosinase.